Cellulosic fraction of rice bran fibre alters the conformation and inhibits the activity of porcine pancreatic lipase. (December 2015) - Qi, Jing; Li, Yue; Yokoyama, Wallace; Majeed, Hamid; Masamba, Kingsley George; Zhong, Fang; Ma, Jianguo
Highlights: RBIDF-2.0 showed the highest lipase adsorption with greater specific surface area. RBIDF physicochemical properties were dependent on the level of acid treatment. Adsorbed and unabsorbed PL activity was independent of its quantity. Moderate modification of RBIDF had the greatest inhibitory effect on PL. PL and RBIDF interaction was hydrophobic, electrostatic and is spontaneous and exothermic. Abstract: A cellulosic rice bran insoluble dietary fibre (RBIDF) with different structures and physicochemical properties is shown to inhibit the activity of pancreatic lipase (PL) at different levels. The adsorption rate and saturation level to PL were greatest for RBIDF-2.0 (modified with 2.0% H2 SO4  + 1.25% KOH), which had the highest specific surface area and oil holding capacity. The conformational deformation of unbound PL in the supernatant of PL-RBIDF confirmed by circular dichroism (CD) suggested that not only bound but also unbound PL activities were altered. Free energy calculations using data from fluorescence spectroscopy revealed that binding of PL to fibre depends primarily on electrostatic interactions, and the binding process is spontaneous and exothermic. This study indicates that dietary intake of cellulosic fractions of rice bran may be useful in reducing the bioavailability of dietary fat by altering the conformation and activity of PL that might be useful to control obesity.